Performance and reaction mechanisms of tin compounds as high-capacity negative electrodes of lithium and sodium ion batteries. Issue 6 (21st February 2022) - Kotaka, Hiroki; Momida, Hiroyoshi; Oguchi, Tamio
Abstract : We study the rechargeable Li and Na ion battery characteristics of tin sulfide (SnS) and tin phosphate (Sn4 P3 ) as negative electrodes by first-principles calculations. Abstract : We study the characteristics of tin sulfide (SnS) and tin phosphate (Sn4 P3 ) as negative electrodes for rechargeable Li and Na ion batteries by first-principles calculations. The electrode reaction formulae during the discharge processes are fully revealed by the energy analyses of ternary A–Sn–B (A = Li, Na; B = S, P) phase diagrams. The phase diagrams of ternary systems with the constructed convex-hull surfaces show a possible reaction route considering intermediate products in discharge reactions. The voltage–capacity curves along the reaction paths obtained from the ternary phase diagrams are calculated. To evaluate the battery performance of tin compounds, we analyze the volume expansion ratios of the materials by incorporation of Li and Na ions. In the case of Li/SnS, Na/SnS, and Li/Sn4 P3, it is found that the conversion reactions and subsequently the alloying reactions proceed stepwise in the electrode, contributing to their high capacities. In Na/Sn4 P3, however, the conversion and alloying reactions proceed alternately or simultaneously, showing more complex reactions than the others.